ANALYSIS OF THE DETERMINANTS OF MALNUTRITION AMONG CHILDREN UNDER FIVE IN THE REGENCIES AND CITIES OF BALI PROVINCE, 2019–2023 - Caroeliene Mutiara Diva Savitri; Ni Nyoman Yuliarmi (Adisam Publisher, 2025)
Malnutrition is a condition caused by an imbalance between what a person eats and what is needed to maintain good health. Malnutrition remains one of the major public health issues, especially in developing countries, affecting infants, toddlers, and women of reproductive age. The purpose of this study is to analyze both simultaneously and partially the effects of economic growth, healthcare facilities, environmental sanitation, women's education level, and poverty on the number of malnourished toddlers in the regencies/municipalities of Bali Province. The study covers the period from 2019 to 2023 and uses panel data, which is a combination of time series and cross-sectional data. The results of the study indicate that simultaneously, economic growth, healthcare facilities, environmental sanitation, women's education, and poverty have a significant effect on malnutrition. Partially, economic growth has a negative and significant effect, poverty has a positive and significant effect, while healthcare facilities, environmental sanitation, and women's education level have negative but not significant effects on malnutrition. It is expected that this study can provide incentives for policymakers in strengthening posyandu (integrated health post) programs that directly target toddlers across all social groups.